Factors Causing The Use Of Intrauterine Device (IUD) Contraceptives In Couples Of Childbearing Age - Wiwi Wardani Tanjung (Institute of Computer Science (IOCS), 2021)
The Use of the Intra Uterine Device (IUD) in couples of childbearing age is still a major concern and has become a big problem for the health of countries in the world including developing countries. The purpose of this research was to determine the factors causing the use of the IUD in couples of childbearing age in Desa Gunung Hasahatan Kecamatan Padangsidimpuan Batunadua Kota Padangsidimpuan. This type of research is quantitative with a cross-sectional study design. The sample in this study was as many as 49 people. The sampling technique used in this study was purposive sampling. The Data was analyzed by univariate and bivariate used the Chi-Square test. The results showed that there was a relationship between the causes of age (p = 0.036), parity (p = 0.046), knowledge (p = 0.019) with the used of the IUD contraceptive. Expected to health workers to further enhance health promotion efforts especially about contraceptive IUD intensively through direct communication to the community with involve husband and family